2021
DOI: 10.1111/apt.16567
|View full text |Cite
|
Sign up to set email alerts
|

Progressive alcohol‐related liver fibrosis is characterised by imbalanced collagen formation and degradation

Abstract: Summary Background Liver fibrosis accumulation is considered a turnover disease, with formation exceeding degradation, although this hypothesis has never been tested in humans. Aims To investigate extracellular matrix (ECM) remodelling in a biopsy‐controlled study of alcohol‐related liver disease (ALD) patients. Methods We evaluated the relationship between formation and degradation of four collagens as a function of histological fibrosis, inflammation and steatosis in 281 patients with ALD and 50 matched heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 25 publications
5
17
0
1
Order By: Relevance
“…Our analyses of the net deposition ratio of PRO‐C3 and C3M in the hepatic blood showed that the ratio between the two also increased with the liver fibrosis stage at baseline. This confirms another recent study by our group where turnover, in general, was found to be increased in patients with ALD 26 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our analyses of the net deposition ratio of PRO‐C3 and C3M in the hepatic blood showed that the ratio between the two also increased with the liver fibrosis stage at baseline. This confirms another recent study by our group where turnover, in general, was found to be increased in patients with ALD 26 …”
Section: Discussionsupporting
confidence: 93%
“…PRO‐C3 displays high diagnostic accuracy of advanced fibrosis and predicts fibrosis progression and outcomes in several liver disease etiologies 15,22‐26 . In our study, PRO‐C3 increased in all three study groups within 24 hours, and when liver‐diseased patients were divided according to the aetiological background.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Assessment of liver fibrosis -Fibrosis is not a disease but rather an outcome of the tissue repair response that becomes dysregulated following many types of chronic liver injury and results in accumulation of extracellular matrix proteins, primarily collagen and fibronectin, the structural component of fibrosis and cirrhosis [36,37,38]. Liver fibrosis represents the early pre-cirrhotic stages of chronic liver disease, which in general is asymptomatic and characterized by slow progression through years to decades [6].…”
Section: Clinical Approach To Diagnosis Of Early Alcohol Related Liver Diseasementioning
confidence: 99%